Transparency of the Vote Counting Recapitulation for the 2024 Legislative Election in West Java Province - Istianah, Ratna; Arsyad, Armin; Kambo, Gustiana (Universitas Muhammadiyah Makassar, 2025)
The vote count recapitulation is a crucial stage in the election process because it determines the conversion of voters' votes into official election results. Transparency at this stage is a crucial prerequisite for maintaining the integrity and legitimacy of election results. This study aims to analyze the transparency of the vote count recapitulation for the 2024 Indonesian House of Representatives (DPR RI) Legislative Election in West Java Province. The study used a qualitative method with a descriptive approach. Data were obtained through literature and documentation studies, including laws and regulations, official documents from election organizers and supervisors, and relevant scientific literature. Data analysis was conducted descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the transparency of the vote count recapitulation in West Java Province has been implemented in accordance with normative provisions, but is not yet fully substantive. The transparency of the process is still limited to the internal scope of election administration, while public access and publication of recapitulation documentation are not yet evenly distributed. The use of information technology in vote count recapitulation also does not fully guarantee the transparency of the process. This study concludes that strengthening the transparency of the vote count recapitulation is necessary to improve the quality of election governance and public trust in the results of the Legislative Election